Ukraine and the end of civilian innocence - Petersen, Karen Lund (Politica, 2023)
Several US think tanks and newspapers have described the current security situation in Ukraine as marking a new world order – a post-post Cold War – in which Russia and China have entered the scene as major powers, and where the EU’s internal power relations are consolidated and strengthened. However, the description of this new reality of great power rivalry is only part of the picture that emerges. The fact of the matter is that our ideas about how to combat threats and who is responsible for this fight have fundamentally changed. Today’s geopolitics are not only fought by states, within the framework of diplomacy and military institutions, but also by Danish and other Western companies. This article examines what characterizes the role of Danish companies in Danish security politics and what this development means for our understanding of security politics in the coming years.